2015
DOI: 10.1055/s-0034-1544112
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Finding of Schwannoma of the Vidian Canal: A Case Report

Abstract: Background Schwannomas of the vidian canal are an extremely rare type of intracranial tumor that can have variable clinical presentations including headache, facial pain, facial muscle paralysis, decreased lacrimation, or nasal dryness. We present an atypical case of an incidentally identified asymptomatic vidian canal schwannoma. Case Description A 49-year-old woman with a history of multiple sclerosis presented for routine surveillance magnetic resonance imaging that detected an ovoid mass originating in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The relationship between the vidian canals and the foramen rotundum was studied before [5] and the findings of this study corroborate ours with respect to the mean of the distances found here. These authors, however, did not consider in their sample those cases in which the channels were double and thus a discrepancy of results could occur if double measurements were performed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The relationship between the vidian canals and the foramen rotundum was studied before [5] and the findings of this study corroborate ours with respect to the mean of the distances found here. These authors, however, did not consider in their sample those cases in which the channels were double and thus a discrepancy of results could occur if double measurements were performed.…”
Section: Discussionsupporting
confidence: 90%
“…One of its advantages is also cited as a lower radiation dose when compared to fan beam tomography. Its use in dentistry, as well as in specialties such as otolaryngology, has grown significantly in recent decades [5,6].…”
Section: Cone-beammentioning
confidence: 99%
“…Vidian nerve schwannomas are extremely rare lesions and only seven cases have been reported in the literature. 1 , 2 , 3 , 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%